The Influence of Canva-Based Learning Media on Creativity and Critical Thinking of Vocational School Students - Aini Zakiyah; Kustiyowati; Waris (Postgraduate, University of Mataram, 2024)
The creativity and critical thinking of class XI students at SMK Plus Bustanul Ma'arif is still relatively low. One of the reasons for this is that teachers in carrying out learning do not use media. The aim of this research is to describe the influence of Canva-based learning media on the creativity and critical thinking of class XI students at SMK Plus Bustanul Ma'arif. The method used is Quasi Experiment with a Pretest-Posttest Only Control Group Design. The research instruments used were creativity and critical thinking tests. The homogeneity test results show that the sig value. creativity of 0.115 and a sig value. critical thinking is 0.773, so it can be concluded that the sample variance is homogeneous. Meanwhile, the normality test results show that the sig. creativity and critical thinking in the control group and experimental group were normally distributed because > 0.05. After fulfilling the prerequisite tests, the researcher collected posttest data on creativity and critical thinking in the control class and experimental class which were analyzed using the MANOVA test with an error degree of 5%. The results show that there is the significant influence of Canva-based learning media on the creativity and critical thinking of class XI students at SMK Plus Bustanul Ma'arif; Ha accepted and rejected H0.